Patient perspective on predictive models in healthcare: translation into practice, ethical implications and limitations? - Sarah Markham (BMJ Health & Care Informatics)
In this perspective article, we consider the use of predictive models in healthcare and associated challenges. We will argue that patients can play a valuable role in supporting the safe and practicable embedding of such tools and provide some examples.